2010
DOI: 10.1016/j.tem.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

JNK regulation of hepatic manifestations of the metabolic syndrome

Abstract: Nonalcoholic fatty liver disease (NAFLD) is now recognized as both an important component of the metabolic syndrome and the most prevalent liver disease in the United States. Although the mechanisms for development of steatosis and chronic liver injury in NAFLD remain unclear, recent investigations have indicated that overactivation of c-Jun N-terminal kinase (JNK) is critical to this process. These findings, together with evidence for the involvement of JNK signaling in other manifestations of the metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 69 publications
(109 reference statements)
2
93
0
1
Order By: Relevance
“…Although this inconsistency in mechanism for cancer and metabolic disorders currently remains unexplored, the downstream signaling activated by periostin might be cell or tissue specific. In addition, studies using genetically engineered mice have shown that hyperactivation of the JNK pathway contributes to the development of metabolic diseases, including hepatic steatosis, obesity, and insulin resistance (36)(37)(38). Consistent with this, strong activation of JNK has been observed in the livers of HFD-fed mice and genetically obese mice (39,40).…”
Section: Disruption Of Postn Improves Hepatosteatosis In Obese Micementioning
confidence: 67%
“…Although this inconsistency in mechanism for cancer and metabolic disorders currently remains unexplored, the downstream signaling activated by periostin might be cell or tissue specific. In addition, studies using genetically engineered mice have shown that hyperactivation of the JNK pathway contributes to the development of metabolic diseases, including hepatic steatosis, obesity, and insulin resistance (36)(37)(38). Consistent with this, strong activation of JNK has been observed in the livers of HFD-fed mice and genetically obese mice (39,40).…”
Section: Disruption Of Postn Improves Hepatosteatosis In Obese Micementioning
confidence: 67%
“…It is important to distinguish interruption of hyperactivation of hepatocellular JNK/c-Jun/ AP-1 signaling from a complete abolishment of JNK in hepatocytes, as mice with specific ablation of Jnk1 in hepatocytes surprisingly exhibit glucose intolerance, insulin resistance and hepatic steatosis. 9 Moreover, we have shown that c-Jun abundance is a critical pathogenic factor in malignant melanoma independent of JNK activation. 56 There, c-Jun levels are regulated at the post-transcriptional level by micro RNA (miR) 125b.…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, we found enhanced c-Jun levels, and this observation was confirmed in human tissues, too. The activity of c-Jun N-terminal kinases (JNKs) and herewith c-Jun activation have been implicated in NASH progression, 8,9 but abundance of c-Jun in NAFLD has not been describe before.…”
mentioning
confidence: 99%
“…In contrast to 3 mo, 7 mo-long high fat intake increased aSMA expression in the livers of both floxed and knockout mice ( Figure 7A). Studies with JNK knockout mice fed with methioninecholine-deficient diet (MCD) diets have indicated a role for c-Jun N-terminal kinase (JNK) in steatosis [42] . JNK is activated by phosphorylation on serine residues [43] .…”
Section: Resultsmentioning
confidence: 99%